2024
DOI: 10.1177/00368504241228077
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of conventional orthodontic radiographic modalities and cone-beam computed tomography for localization of impacted maxillary canine teeth

Behzad Salari,
Maryam Tofangchiha,
Parviz Padisar
et al.

Abstract: Background: Orthodontic treatment planning for an impacted canine tooth requires accurate information about its position. The aim of this study was to compare the diagnostic accuracy of two conventional orthodontic radiographic modalities with cone-beam computed tomography (CBCT) for localization of impacted maxillary canine teeth. Materials and Methods: Panoramic radiographs, lateral cephalograms, and CBCT scans of 30 patients with unilaterally impacted maxillary canine teeth were retrieved from the archives.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Recent studies showed that psychosocial factors such as stress, anxiety, alexithymia, and catastrophizing could affect the onset of TMD and its response to treatment (De la Torre Canales et al, 2020 ; Rollman & Gillespie, 2000 ; Sadrzadeh‐Afshar et al, 2023 ; Shahnavazi et al, 2021 ). Different malocclusions have also been a controversial risk factor for TMD (Manfredini et al, 2017 ; Salari et al, 2024 ). The diagnosis is based on clinical examinations, past medical and dental history, and paraclinical data (Daniele Kapos et al, 2020 ; Manfredini et al, 2023 ; Padisar et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies showed that psychosocial factors such as stress, anxiety, alexithymia, and catastrophizing could affect the onset of TMD and its response to treatment (De la Torre Canales et al, 2020 ; Rollman & Gillespie, 2000 ; Sadrzadeh‐Afshar et al, 2023 ; Shahnavazi et al, 2021 ). Different malocclusions have also been a controversial risk factor for TMD (Manfredini et al, 2017 ; Salari et al, 2024 ). The diagnosis is based on clinical examinations, past medical and dental history, and paraclinical data (Daniele Kapos et al, 2020 ; Manfredini et al, 2023 ; Padisar et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Different malocclusions have also been a controversial risk factor for TMD (Manfredini et al, 2017;Salari et al, 2024). The diagnosis is based on clinical examinations, past medical and dental history, and paraclinical data (Daniele Kapos et al, 2020;Manfredini et al, 2023;Padisar et al, 2020).…”
mentioning
confidence: 99%